Novel phenotype–genotype correlations of hypertrophic cardiomyopathy caused by mutation in α-actin and myosin-binding protein genes in three unrelated Chinese families. Issue 5 (May 2019) - Yang, Qian-Li; Bian, Yang-Yang; Wang, Bo; Zuo, Lei; Zhou, Meng-Yao; Shao, Hong; Zhang, Yan-Min; Liu, Li-Wen
Highlights: ACTC1 -D26N was classified as likely pathogenic for hypertrophic cardiomyopathy (HCM) according to American College of Medical Genetics and Genomics guidelines. Patients with ACTC1 -D26N were non-obstructive hypertrophic cardiomyopathy (non-obstructive HCM), with high penetrance, and diverse phenotypes. Echocardiography showed patients often had left atrial remodeling and L-wave filling pattern. A second mutation MYBPC3 -R215C may represent a new feature on HCM phenotype. Abstract: Background: The correlations between genotype and phenotype in hypertrophic cardiomyopathy (HCM) have not been established. Mutation of α-actin gene ( ACTC1 ) is a rare cause of HCM. This study aimed to explore novel genotype–phenotype correlations in HCM patients with the variants in ACTC1 and myosin-binding protein ( MYBPC3 ) genes in three unrelated Chinese families. Methods: Clinical, electrocardiographic, and echocardiographic examinations were performed in three Han pedigrees. Exon and boarding intron analysis of 96 cardio-disease-related genes was performed using second-generation sequencing on three probands. The candidate variants were validated in 14 available family members and 300 unrelated healthy controls by bi-directional Sanger sequencing. The pathogenicity and conservation were calculated using MutationTaster, PolyPhen-2, SIFT, and Clustal X. Pathogenicity classification of the variants was based on American College of Medical Genetics and Genomics (ACMG) guidelines. Results: Nine members fulfilled diagnostic criteria for HCM with clinical characteristics, electrocardiographic, and echocardiographic findings. Two candidate variants in ACTC1 p.Asp26Asn ( ACTC1 -D26N) and MYBPC3 p.Arg215Cys ( MYBPC3 -R215C) were identified in patients. Only ACTC1 -D26N strongly co-segregated with the HCM phenotype. Seven patients who harbored variant ACTC -D26N only were diagnosed with non-obstructive HCM, and four of these patients exhibited a triphasic left ventricular (LV) filling pattern. Two patients carrying both ACTC1 -D26N and MYBPC3 -R215C variants showed a higher LV outflow tract pressure gradient. Bioinformatics analysis revealed that the two variants were deleterious and highly conserved across species. According to ACMG guidelines, ACTC1 -D26N is classified as a likely pathogenic mutation. The second variation MYBPC3 -R215C may function as a genetic modifier, which remains uncertain here. Conclusions: Novel p.(Asp26Asn) mutation of ACTC1 was associated with HCM phenotype, and the penetrance is extremely high (∼81.8%) in adults. The second variation, MYBPC3 -R215C may function as a genetic modifier, which remains uncertain here.